Multi-physics Coupling Analysis of Clayey Core Wall of High Earth-Rockfill Dam - Wu, Yongkang (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2019)
Nominated by Tsinghua University as an outstanding Ph.D. thesis, this book investigates the mechanical properties of unsaturated compacted clayey soil, the multi-field coupling consolidation theory of unsaturated soil and its application to a 261.5 m high earth-rockfill dam. It proposes a multi-field coupling analysis method of consolidation, and develops an efficient and practical finite element (FE) program for large-scale complex earth-rockfill dams. The book is primarily intended for researchers studying the multi-field coupling analysis of seepage consolidation.